2022
DOI: 10.3390/plants12010044
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Regulates Antioxidant, Photosynthesis, and Cell Permeability in Plants under Various Abiotic Stresses: A Review

Abstract: Plant growth is affected by various abiotic stresses, including water, temperature, light, salt, and heavy metals. Selenium (Se) is not an essential nutrient for plants but plays important roles in alleviating the abiotic stresses suffered by plants. This article summarizes the Se uptake and metabolic processes in plants and the functions of Se in response to water, temperature, light, salt, and heavy metal stresses in plants. Se promotes the uptake of beneficial substances, maintains the stability of plasma m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 147 publications
0
10
0
Order By: Relevance
“…In the occurrence of drought stress, the interconversion and accumulation of reactive oxygen species such as hydroxide ions (OH − ), superoxide anions (O 2− ), hydroxyl radicals (-OH), and hydrogen peroxide (H 2 O 2 ) are induced to activate the antioxidant system of the plant, which contributes to the up-regulation or down-regulation of antioxidant enzyme activities [ 24 , 25 ] in order to mitigate the effects of oxidative stress in the plant. Meanwhile, plants will maintain cell expansion pressure by accumulating osmoregulatory substances (osmoregulation is an adaptive response of crops to tolerate and resist drought stress [ 23 ]) to reduce cellular osmotic potential and regulate crop tolerance to low water potential [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the occurrence of drought stress, the interconversion and accumulation of reactive oxygen species such as hydroxide ions (OH − ), superoxide anions (O 2− ), hydroxyl radicals (-OH), and hydrogen peroxide (H 2 O 2 ) are induced to activate the antioxidant system of the plant, which contributes to the up-regulation or down-regulation of antioxidant enzyme activities [ 24 , 25 ] in order to mitigate the effects of oxidative stress in the plant. Meanwhile, plants will maintain cell expansion pressure by accumulating osmoregulatory substances (osmoregulation is an adaptive response of crops to tolerate and resist drought stress [ 23 ]) to reduce cellular osmotic potential and regulate crop tolerance to low water potential [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, measuring the amount of electrolyte leakage is one of the good indicators for measuring the amount of oxidative damage to the membrane. Due to the cytoplasmic membrane’s vulnerability, the cell’s contents leak out, and the amount of this damage is determined by measuring electrolyte leakage [ 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationship between the absorption of Se with phosphorylation and ATP binding in plants is unknown. Nevertheless, studies have shown that Se can regulate photosynthesis in plants ( Liu et al., 2022 ). Photophosphorylation is the process by which ADP is phosphorylated to form ATP using sunlight.…”
Section: Discussionmentioning
confidence: 99%